"I think everybody will have to get together for it to work": NYCHA Tenant Perspectives on HUD's 2018 Smoke-Free Mandate Captured Prior to Policy Implementation. Issue 10 (24th March 2022) - Mohindra, Mandakini; Hernández, Diana
Abstract: Introduction: In July 2018, a new federal mandate by the Department of Housing and Urban Development went into effect requiring all US public housing authorities to implement policies banning smoking in living units, indoor common areas, administrative buildings, and outdoor areas within 25 feet of these buildings. Although some housing authorities had smoke-free policies in place for decades, others had to implement them for the first time. Housing authorities continue to face challenges in ensuring compliance with these policies, and resident perspectives can greatly inform measures to promote adherence. Aims and Methods: We conducted in-person interviews with 20 New York City Housing Authority tenants in April 2018. Our thematic analysis examined resident opinions on the upcoming smoke-free housing policy. Results: Although 65% of residents supported the policy, 50% anticipated poor adherence due to expected lack of enforcement, safety issues with smoking outdoors, and general discontent with the housing authority and living conditions. However, many participants felt adherence could be improved if the housing authority optimized resource-provision and communication with tenants. Conclusions: Our study adds to existing literature examining tenant views on the controversial topic of mandatory smoke-free housing policies, and our interviews were conducted at a unique time prior to policy implementation in the country's largest public housing authority. Based on our results, we provide recommendations for housing authorities including: (1) information and resource-provision, (2) safety enhancement, and (3) relationship building with tenants in order to maximize policy adherence. Implications: Our study is unique because we captured resident views prior to policy implementation in a housing authority without a preexisting smoke-free policy in place. In comparison, most recent research on this topic has focused on the postimplementation period or used survey research methods in the preimplementation phase. Our findings add to extant research about tenant perspectives on smoke-free housing policies and offer suggestions to address barriers to compliance.